Influence of Brand Image, Price, and Promotion Regarding the Purchase Decision of Mineral Water Brand Me Water in Martapura, Banjar District, South Kalimantan - Kadir, Abdul; Audah, Ali; Jayen, Fredy; Amrulloh, Rifqi; Naimah (Archives of Business Research, 2023)
This study aims to analyze the simultaneous and partial influence of brand image, price and promotion on purchasing decisions of Me Water brand bottled drinking water in Martapura, Banjar Regency. The population in this study were consumers who consumed packaged drinking water with the Me Water brand in Martapura, Banjar Regency. Determination of the number of samples using the Isac Michel formula, with a 95% confidence level, the number of samples is 97 people. This research is research with a quantitative research design. Data collection techniques using questionnaires, documentation, interviews and observation. Validity test, reliability test, normality test, multicollinearity test and heteroscedasticity test were carried out on research instruments. Data were analyzed by multiple linear regression analysis. The results of the study show that brand image, price and promotion simultaneously and partially influence purchasing decisions. The test results of the coefficient of determination of brand image, price and promotion have a very strong relationship with purchasing decisions, namely brand image, price and promotion can influence purchasing decisions by 91.5%